Controlling rogue wave triplets in Bose–Einstein condensate. (14th April 2015) - Loomba, Shally; Pal, Ritu; Kumar, C N
Abstract: We present the coherent control of rogue wave triplets in Bose–Einstein condensate (BEC) for the parametric choices which support their occurrence experimentally. This analysis has been done for two cases involving the trapping of BEC in (i) time-independent (ii) time-dependent harmonic potential. We have found that these waves no longer lie on the apex of the equilateral triangle as in the case of homogeneous system but can be manipulated by modulating the trap. This enables us to control the relative distance among the three rogue wave peaks and their amplitude, for a given nonlinearity parameter. These results can be helpful to stimulate the study of rogue wave triplets experimentally in BEC.